Editor's Comment and Q&A - Miamoto, Cristina Batista; Ramos-Jorge, Maria Leticia; Pereira, Luciano José; Paiva, Saul Martins; Pordeus, Isabela Almeida; Marques, Leandro Silva (American journal of orthodontics and dentofacial orthopedics, 2010)
Our aims in this study were to compare the biopsychosocial aspects of patients with cerebral palsy and subjects in a control group, establish the severity of malocclusion, and identify determinant factors. The group with cerebral palsy included 60 patients diagnosed with the spastic form of the disease. The control group included 60 randomly selected healthy subjects with various malocclusions. Data were collected through questionnaires, medical charts, and clinical evaluations. The criteria of the dental aesthetic index were used for the diagnosis of malocclusion. Comparisons between groups and between the independent variables and dependent variable (severity of malocclusion) were performed by using the chi-square test (P ≤0.05) and multivariate logistic regression (forward stepwise procedure). Significant differences between the groups were found for these variables: tooth loss, overjet, anterior open bite, facial type, breathing pattern, drooling, difficulty in swallowing, and lip incompetence. The main risk factors associated with the severity of malocclusion were cerebral palsy, mouth breathing, lip incompetence, and long face.